KAJIAN ASPEK PERTUMBUHAN DAN LAJU EKSPLOITASI IKAN TERI NASI (Stolephorus spp.) DI PERAIRAN BELAWAN SUMATERA UTARA Aspects of Growth Study and Exploitation Rate Anchovy (Stolephorus spp.) in Belawan Waters of North Sumatra - Zefri Ade Gurukinayan; Yunasfi Djayus; Ahmad Muhtadi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Anchovy (Stolephorus spp.) is an abundant fishery resources in the watersof Indonesia. These fish include small pelagic fish. Until now, studies on thepopulation dynamics of anchovy is still low, especially in Belawan waters. Thisstudy aims to determine the aspects of growth and the rate of exploitation ofanchovy. Location of research conducted around Aquatic Belawan. Anchovytaken as much as 0.001% of catches depending on the abundance of each monthby taking 1-month intervals for 12 months. Analysis of data using a supportprogram Ms. Exel and software FISAT II Ver 1.1.0. The results showed that thelength of anchovy were captured during the study ranged 24.5-26.5 mm. Growthtype of anchovy is allometric positive. Factor in the range of conditions0.030396–0.318734. Alleged growth coefficient 0.890/year, maximum length(L∞) 39.18 mm and the theoretical age at the time of the fish length is equal tozero (t0) is -0.60. Total mortality 4.760, mortality catching 3.199 and naturalmortality 1.560. The rate of exploitation is 0.68 who is alleged to have occurredoverexploitation. This information can be used as the basis of the managementalternative arrangements fishing season, restrictions on catches, setting the meshso that the fish remain stable.Keywords: Anchovy, Pattern Growth, Exploitation, Management.